Peptides from Tetraspanin CD9 Are Potent Inhibitors of Staphylococcus Aureus Adherence to Keratinocytes - Ventress, Jennifer K.; Partridge, Lynda J.; Read, Robert C.; Cozens, Daniel; MacNeil, Sheila; Monk, Peter N. (PLOS ONE, 2016)
Staphylococcus aureus is one of the primary causative agents of skin and wound infections. As bacterial adherence is essential for infection, blocking this step can reduce invasion of host tissues by pathogens. An anti-adhesion therapy, based on a host membrane protein family, the tetraspanins, has been developed that can inhibit the adhesion of S. aureus to human cells. Synthetic peptides derived from a keratinocyte-expressed tetraspanin, CD9, were tested for anti-adhesive properties and at low nanomolar concentrations were shown to inhibit bacterial adhesion to cultured keratinocytes and to be effective in a tissue engineered model of human skin infection. These potential therapeutics had no effect on keratinocyte viability, migration or proliferation, indicating that they could be a valuable addition to current treatments for skin infection.